Positive and Negative Themes in Popular Video Games Based on Entertainment Software Review Board Ratings - Fady Ghattas BA; Lilia Reyes MD (SAGE Publishing, 2019)
Video games have become a major part of a child's recreational time. The objective of this study was to determine whether or not the number of positive and negative themes in video games differ based on their Entertainment Software Review Board rating. Thirty of the most popular games in 2016 were reviewed and scored based on a rubric made a priori. Mature, Teen, and Everyone rated games did not show significant difference in the frequency of positive themes (3.7, 3.1, 3.2, respectively; P = .425). Mature and Teen games did not show significant difference in the frequency of negative themes (5.0, 4.0, respectively; P = .414), whereas Everyone games did have a significantly less number of negative themes than the Mature games (1.9, 5.0, respectively; P = <.001). Based on these data, parents should consider being more conscientious in buying games that are rated as T for Teen.